Histories of Post-Mortem Contagion Infectious Corpses and Contested Burials (Medicine and Biomedical Sciences in Modern History, 2018)
This edited volume draws historians and anthropologists together to explore the contested worlds of epidemic corpses and their disposal. Why are burials so frequently at the center of disagreement, recrimination and protest during epidemics? Why are the human corpses produced in the course of infectious disease outbreaks seen as dangerous, not just to the living, but also to the continued existence of society and civilization? Examining cases from the Black Death to Ebola, contributors challenge the predominant idea that a single, universal framework of contagion can explain the political, social and cultural importance and impact of the epidemic corpse. .